DETERMINATION OF THE QUALITY INDEX OF CARS - Oleksiy BAZHINOV; Mikhail KRAVTSOV; Tetiana BAZHYNOVA; Yevhen HAIEK; Serhii KHARCHENKO; Taras SHCHUR; Katarzyna MARKOWSKA; Agnieszka SĘKALA; Kinga STECUŁA; Tomasz KAWKA; Ewa SIUDYKA (Scientific Journal of Silesian University of Technology. Series Transport)
This article presents theoretical studies of methods for assessing car quality indicators in the operation stage. Important criteria for determining the quality indicators of cars during the operation phase are the following: functional stability, ecology, comfort, technical solutions, and traffic safety. The problem of converting a multicriteria quality assessment to a single criterion is proposed to be solved by the method of determining a quality index. The methodology for the practical and actual implementation of this research is based on the evaluation of the quality index established on the average vehicle speed then the basic methodological principles are formulated. The quality index of a car is significantly dependent on the operating conditions. This article presents the correction coefficients for the quality index of base, hybrid, and electric vehicles, depending on the operating conditions. The studies and the proposed car quality index provide timely information on the characteristics of operating conditions, creating the necessary conditions and opportunities for automakers to improve the design of cars, promote the image of car brands, and increase sales.